Edukasi preventif dan promotif dalam upaya pencegahan stunting di Desa Tuncung Kecamatan Maiwa Kabupaten Enrekang - Syamson, Meriem Meisyaroh; Zainab, Zainab; Hasanuddin, Indirwan; Sulaeman, Sulaeman; Purnama AL, Jumiarsih; Murtini, Murtini; Faridah, Faridah; Suparta, Suparta (JOURNAL OF Public Health Concerns, 2025)
Background: Stunting is a public health problem that is still a serious challenge in Indonesia. Stunting occurs due to chronic malnutrition which causes children to have a lower height compared to children of the same age. The prevalence of stunting in Indonesia is still quite high, although efforts to reduce it have been carried out nationally. This condition not only has an impact on children's physical condition, but also affects their cognitive development, immunity, and productivity in the future. Purpose: To provide education with a preventive approach and a promotive approach to the community in an effort to prevent stunting incidents in a sustainable manner. Method: The target of this activity is all residents of Tuncung Village, especially housewives and those with babies and children. On Wednesday, January 8, 2025, at the Tuncung Village Hall, Maiwa District, Enrekang Regency. Counseling by providing information directly by health workers or facilitators to the community in the form of lectures to provide basic knowledge about stunting, such as causes, impacts, and how to prevent it Results: The participants gave a positive response by attending and following each activity session, were able to provide simulation actions according to the instructions after gaining knowledge from the presentation of the material provided by the resource person, understood efforts to prevent stunting with awareness as preventive measures such as fulfilling balanced nutrition, good parenting patterns, and environmental cleanliness, understood promotive efforts in reducing the incidence of stunting by changing positive behavior, namely playing an active role in monitoring the growth and development of children through routine visits to health facilities. Conclusion: Education and preventive approaches provide increased knowledge in identifying and reducing the risk of stunting early on. Meanwhile, promotive education increases public awareness of the importance of a healthy lifestyle, exclusive breastfeeding and good parenting in supporting child growth and development in an effort to prevent stunting. Preventive and promotive education will reduce stunting incidents sustainably. Suggestion: Introduce the concept of "Isi Piringku" for toddlers so that parents understand the adequacy of nutritional intake needed by children according to their growth and development. Cadres, community leaders, religious organizations, or schools can provide information to the wider community about the importance of preventing stunting incidents and the impacts of stunting. Local companies in supporting CSR programs are expected to focus on stunting eradication, such as providing nutritious food for underprivileged children. Keywords: Education; Preventive; Promotive; Stunting Pendahuluan: Stunting merupakan salah satu masalah kesehatan masyarakat yang masih menjadi tantangan serius di Indonesia. Stunting terjadi akibat kekurangan gizi kronis yang menyebabkan anak memiliki tinggi badan yang lebih rendah dibandingkan dengan anak seusianya. Prevalensi stunting di Indonesia masih cukup tinggi, meskipun upaya penurunan telah dilakukan secara nasional. Kondisi ini tidak hanya berdampak pada fisik anak, tetapi juga memengaruhi perkembangan kognitif, imunitas, dan produktivitas mereka di masa depan. Tujuan: Memberikan edukasi dengan pendekatan preventif dan pendekatan promotif  pada masyarakat dalam upaya mencegah kejadian stunting secara berkelanjutan. Metode: Sasaran kegiatan ini adalah seluruh warga Desa Tuncung, khususnya ibu rumah tangga dan yang mempunyai bayi dan anak. Pada Hari Rabu, 08 Januari 2025, bertempat di Balai Desa Tuncung, Kecamatan Maiwa Kabupaten Enrekang. Penyuluhan dengan pemberian informasi secara langsung oleh tenaga kesehatan atau fasilitator kepada masyarakat dalam bentuk ceramah untuk memberikan pengetahuan dasar tentang stunting, seperti penyebab, dampak, dan cara pencegahannya Hasil: Para peserta memberikan respon positif dengan menghadiri dan mengikuti setiap sesi kegiatan, dapat memberikan tindakan simulasi sesuai dengan petunjuk setelah mendapatkan pengetahuan dari paparan materi yang diberikan oleh nara sumber, memahami upaya pencegahan kejadian stunting dengan kesadaran sebagai tindakan preventif seperti pemenuhan gizi seimbang, pola asuh yang baik, serta kebersihan lingkungan, memahami upaya promotif dalam menekan angka kejadian stunting dengan merubah perilaku yang positif yaitu berperan aktif dalam memantau pertumbuhan dan perkembangan anak melalui kunjungan rutin ke fasilitas kesehatan. Simpulan: Edukasi dan pendekatan preventif memberikan peningkatan pengetahuan dalam mengidentifikasi dan mengurangi risiko terjadinya stunting sejak dini. Sedangkan edukasi promotif memberikan peningkatan kesadaran masyarakat tentang pentingnya pola hidup sehat, pemberian ASI eksklusif dan pola asuh yang baik dalam mendukung tumbuh kembang anak dalam upaya mencegah kejadian stunting. Edukasi preventif dan promotif akan menekan kejadian stunting secara berkelanjutan. Saran: Perkenalkan konsep "Isi Piringku" untuk anak-anak usia balita agar orang tua memahami kecukupan asupan gizi yang dibutuhkan anak-anak sesuai dengan pertumbuhan dan perkembangannya. Para kader, tokoh masyarakat, organisasi keagamaan, atau sekolah dapat memberikan informasi ke masyarakat yang lebih luas tentang pentingnya pencegahan kejadian stunting dan dampak stunting. Perusahaan lokal dalam mendukung program CSR diharapkan berfokus pada pengentasan stunting, seperti penyediaan makanan bergizi bagi anak-anak kurang mampu.